Review on Energy Harvesting from Wind-Induced Column Vibrations: Theories, Mechanisms, and Applications - Ateea, Mustafa H.; Abid, Haider J. (Basrah Journal for Engineering Sciences, 2024)
This paper presents an extensive review of energy harvesting from the column vibrations of wind turbines under the influence of wind. The study investigates the underlying theories, mechanisms, and potential applications of such a system. By tapping into the vibrational energy otherwise dissipated in wind turbines, the study proposes an innovative approach to enhance renewable energy generation. Furthermore, the potential benefits of the technology, such as powering remote sensors, vibration damping, structural health monitoring, and increasing wind turbine efficiency and lifespan, are discussed. While the study acknowledges the promise of such an approach, it also emphasizes the need for further research to optimize and integrate these systems effectively into the renewable energy landscape.